(untitled) (Journal of the College of Basic Education, 2022)
At-Tayyib linguistically: (everything with which perfume is fragrant, incense, incense, etc.), (1) and in the tongue: (flavor).It is good if there is no stench in it, and if there is no good smell in it, such as the scent of agarwood, incense, etc.), (2) then it is good.Flavor It is not necessary for him to smell a perfume from it, rather it is sufficient to not smell of the flavor what he dislikes, such as stench orMildew, and other bad smells, so perfume is the desirable scent, whether it is perfume or something else.But most of the single uses (al-tayyib) are indicative of the fragrant smell much more than their indication ofJust an unpleasant smell, in both prose and poetry, including pre-Islamic poetry.